Bioaerosol emissions from open windrow composting facilities : emission characterisation and dispersion modelling improvements - Douglas, Philippa (Cranfield University, 2013)
Bioaerosol emissions from open windrow composting facilities are becoming of increasing concern due to the negative health effects associated with bioaerosols, and the fact that emissions from open windrow facilities are not contained. Current bioaerosol monitoring techniques provide only a snapshot of bioaerosol concentrations spatially and temporally, whereas dispersion models have the potential to offer a more continual overview of bioaerosol levels, alongside existing sampling methods. However, dispersion models have not been successful at accurately predicting bioaerosol concentrations from open windrow composting facilities, generally under predicting concentrations by at least one order of magnitude. This is predominantly due to a lack of knowledge and data surrounding the complex nature of bioaerosol release and transportation, particularly when the compost is agitated. This study aimed to improve the reliability in the outputs of the ADMS dispersion model, specifically in the open windrow composting scenario, by performing several model tests alongside selected input parameter quantification improvements. This involved completing a sensitivity analysis, and a model calibration and validation specific to this scenario for the first time. Results from the sensitivity analysis showed that the use of wet and dry deposition modules is significant, and the majority of model inputs associated with the representation of the source of the emission are sensitive. These findings helped select the model input parameters for quantification improvements. Novel preliminary measurements of bioaerosol temperature, velocity and concentration at the source of composting agitation activities were completed. These values provided more accurate model inputs. Collectively, these results allowed the model to be successfully calibrated, and consequently, validated for the first time for this specific scenario, resulting in model outputs corresponding to within one order of magnitude to measured data. This has helped to generate an initial set of modelling recommendations, allowing modellers to use the ADMS dispersion model in a reliable manner, when applied to the open windrow composting scenario. Eventually, these improved model outputs may be used to predict bioaerosol exposure levels at sensitive receptors, particularly in conditions where current monitoring methods are not feasible.